The Challenge of Invisible Enemies and Risk Mitigation for Parents in Educating Children in the Modern Era - Sugitanata, Arif; Aqila, Sarah; Aminah, Siti; Abdurrasyied, Muhammad Hasyied (Pusat Studi Gender dan Anak Universitas Islam Negeri Antasari Banjarmasin, 2024)
This study explores the hidden challenges faced by parents in educating children in the modern era, referred to as “invisible enemies”, focusing on digital technology, individualism, academic pressure, peer influence and consumerist culture. It develops adaptive and responsive strategies to address these hidden challenges as a guide for parents. Employing a literature study with a qualitative-exploratory-descriptive approach, this research analyses the risks of the modern era in child education using Ulrich Beck's risk society theory framework. The findings reveal that parents face various hidden risks, such as exposure to inappropriate digital content, social pressures that undermine collective values, and challenges in balancing child protection with fostering independence. These align with the risk society theory, characterized by the risks arising from technological advancements and social changes, which are not only physical but also psychosocial. In this context, parents act as risk mitigation agents. Their role encompasses not only protecting children from the negative impacts of these risks but also equipping them with adaptive skills, instilling collective values, providing support for emotional balance and interests and fostering independence. This study contributes scientifically to the development of parenting strategies that are more responsive to the challenges of the modern era. It also offers practical guidance for parents, educators, and policymakers to create a resilient, ethical generation capable of navigating future socio-technological dynamics. Keywords: Children; Modern Era; Parents; Risk Mitigation; Societal Risk Theory